Civic culture: The marriage values of the Catholic Church on the Dayak Tamambaloh marriage tradition - Efriani, Efriani; Dewantara, Jagad Aditya; Sulistyarini, Sulistyarini; Sihaloho, Nahot Tua Parlindungan; Afandi, Afandi; Soeharto, Soeharto (Universitas Negeri Yogyakarta, 2022)
This study has been motivated by the phenomenon of married life facing various challenges of the times. Therefore, this study has taken the topic of the importance of morals in married life, especially in realizing a harmonious and lasting family life. By focusing on Dayak Tamambaloh in Santo Martinus Parish, Sintang Diocese. This study aims to explore the values of marriage customs in light of the moral teachings of the Catholic Church. Dayak Tamambaloh views marriage as a lifelong union of a man and a woman that lasts a lifetime. This Tamambaloh Dayak marriage custom is manifested in the prohibition of adultery, the ideal form of marriage that is heterosexual and has children, and the ban on divorce. The marriage custom of the Dayak Tamambaloh is in line with the nature of marriage in the Catholic Church, which is monogamous and indivisible. This phenomenon has shown the Tamambaloh Dayak as an ethnic group that can adapt their lives to the morality and spirituality of the Catholic Church. Likewise, the Catholic Church has demonstrated a high appreciation for the noble values of the Tamambaloh Dayak culture.